Estimation of central blood pressure waveform from femoral blood pressure waveform by blind sources separation - Gbaoui, Laila; Hoeschen, Christoph; Kaniusas, Eugenijus; Khatib, Saher; Gretschel, Stephan; Wellnhofer, Ernst (Frontiers in Cardiovascular Medicine, 2023)
Central blood pressure cBP is a better indicator of cardiovascular morbidity and mortality than peripheral BP pBP. However, direct cBP measurement requires invasive techniques and indirect cBP measurement is based on rigid and empirical transfer functions applied to pBP. Thus, a development of personalized and well-validated method for non-invasive derivation of cBP from pBP is necessary to facilitate the clinical routine. The purpose of the present study was to develop a novel blind source separation (BSS) tool to separate a single recording of pBP into their pressure waveforms composing its dynamics, to identify the compounds that lead to pressure waveform distortion at the periphery, and to estimate the cBP. The approach is patient-specific, and extracts the underlying blind pressure waveforms in pBP without additional brachial cuff calibration or any a priori assumption on the arterial model.The intra-arterial femoral BPfe and intra-aortic pressure BPao were anonymized digital recordings from previous routine cardiac catheterizations of 8 patients at the German Heart Centre Berlin. The underlying pressure waveforms in BPfe were extracted by the single channel independent component analysis (SCICA). The accuracy of the SCICA model to estimate the whole cBP waveform was evaluated by the mean absolut error (MAE), root mean square error (RMSE), relative RMSE (RRMSE), and the intraclass correlation coefficient (ICC). The agreement between the intra-aortic and estimated parameters including systolic SBP, diastolic DBP, mean arterial pressure MAP and pulse pressure PP was evaluated by the regression and Bland Altman analyses.The SCICA-tool estimated the cBP waveform non-invasively from the intra-arterial BPfe with a MAE of 0.159 ± 1.629, a RMSE of 5.153 ± 0.957 mmHg, a RRMSE of 5.424 ± 1.304 %, and ICC of 0.94. The regression analysis showed a strong linear trend between estimated and intra-aortic SBP, DBP, MAP and PP with R 2 of 0.98, 0.99, 0.99, and 0.97 respectively. The Bland Altman plots demonstrated good agreement between estimated and intraaortic parameters with a mean error and a standard deviation of difference -0.54 ± 2.42 mmHg for SBP, -1.97 ± 1.62 mmHg for DBP, -1.49 ± 1.40 mmHg for MAP, and 1.43 ± 2.79 mmHg for PP.